Handwriting Difficulties: Introducing an Instrument - Fatemeh Hadavandkhani; Hadi Bahrami; Fatemeh Behnia; Mozhgan Farahbod; Masood Salehi (Iranian Rehabilitation Journal, 2008)
Objectives: The main purpose of this study is to produce an instrument for handwriting evaluation and to execute it on mentally retarded (MR) students.